Symmetry and phrase definition:: Ginastera’s First Piano Sonata, op. 22, II mov. - Carballo, Erick (Música em Contexto, 2015)
The article evaluates the usefulness of the twelve-tone analytical approach when applied to the second movement of Alberto Ginastera’s first Piano Sonata, Op. 22 (1952). Based on the results from this evaluation, it postulates a new analytical approach grounded on two main principles. The first principle is the recognition of symmetrical pitch-class sets and their rapport with the establishment of phrase structures. The second principle deals with the combination of tonal and atonal gestures and their interaction with higher levels of tonal organization””levels that, as the analysis shows, are predominantly diatonic.